STRATEGI COLLABORATIVE GOVERNANCE DALAM REFORMASI PELAYANAN PUBLIK - Agung, Magda Faradiba Mauludia (Department of Public Administration, Faculty of Social and Political Science, Universitas, 2025)
Public service reform is a strategic effort aimed at improving service quality through a more efficient, transparent, and participatory bureaucratic system. In this context, collaborative governance emerges as a crucial approach that emphasizes cooperation among government, civil society, the private sector, and non-governmental organizations in the formulation, implementation, and evaluation of public policies. This study uses a descriptive qualitative method to highlight the relevance of collaborative governance as a response to the complexity of public service challenges that cannot be addressed by a single actor alone. Findings indicate that the success of collaborative governance depends on key factors such as trust among stakeholders, shared commitment, inclusive leadership, and participatory decision-making mechanisms. In Indonesia, the application of this strategy still faces challenges, including a closed bureaucratic culture, low public policy literacy, and limited institutional capacity. However, several local innovations demonstrate that effective collaboration can significantly enhance public service delivery. The study recommends institutionalizing collaboration through supportive regulations, strengthening stakeholder capacity, and developing incentive systems to foster cross-sector partnerships. Collaborative governance is thus a vital key to realizing a more responsive, democratic, and sustainable model of public service governance in today’s dynamic policy environment.